Sectoral and poverty impacts of agricultural policy adjustments in Colombia (2015)
We aim to assess the sectoral and poverty impacts of changes in agricultural policy in Colombia. For this, we use an agriculture specialized static computable general equilibrium model, together with a microsimulation model that allows employment to shift between sectors. Results indicate that the sectoral impact from policy changes tends to be small and that it considerably varies across crops. The macro model yields some gains in wages and capital rents, a relatively larger increase in land rents, and limited labor reallocation, together leading to small poverty impacts as calculated through the microsimulation model. The incidence of rural poverty decreases by less than 1% and the same happens to the poverty gap. In addition, poverty reductions are concentrated among households near the middle of the income distribution. © 2015 International Association of Agricultural Economists.